The HDL particle composition determines its antitumor activity in pancreatic cancer: research article - Oberle, Raimund; Kührer, Kristina; Österreicher, Tamina; Weber, Florian; Steinbauer, Stefanie; Udonta, Florian; Wroblewski, Mark; Ben-Batalla, Isabel; Hassl, Ingrid; Körbelin, Jakob; Unseld, Matthias; Jauhiainen, Matti; et al. (Life science alliance, 2022)
Despite enormous efforts to improve therapeutic options, pancreatic cancer remains a fatal disease and is expected to become the second leading cause of cancer-related deaths in the next decade. Previous research identified lipid metabolic pathways to be highly enriched in pancreatic ductal adenocarcinoma (PDAC) cells. Thereby, cholesterol uptake and synthesis promotes growth advantage to and chemotherapy resistance for PDAC tumor cells. Here, we demonstrate that high-density lipoprotein (HDL)-mediated efficient cholesterol removal from cancer cells results in PDAC cell growth reduction and induction of apoptosis in vitro. This effect is driven by an HDL particle composition-dependent interaction with SR-B1 and ABCA1 on cancer cells. AAV-mediated overexpression of APOA1 and rHDL injections decreased PDAC tumor development in vivo. Interestingly, plasma samples from pancreatic-cancer patients displayed a significantly reduced APOA1-to-SAA1 ratio and a reduced cholesterol efflux capacity compared with healthy donors. We conclude that efficient, HDL-mediated cholesterol depletion represents an interesting strategy to interfere with the aggressive growth characteristics of PDAC.
Gesehen am 02.10.2023